Nilai-Nilai Kepemimpinan Dalam Alkitab: Dari Konteks Sejarah ke Dinamika Era Global - Halawa, Fikarisman (GRAFTA: Journal of Christian Religion Education and Biblical Studies, 2024)
This article discusses leadership values found in the Bible, and how they can be applied in today's global context. Leadership is a manifestation of values, vision, and mission that aligns actions with a greater purpose. The research uses a historical analysis literature approach, to explore examples of leadership found in the Bible, as well as their relevance to modern leadership challenges. Through this study, it is hoped that implications can be found for future leadership that can apply integrity, vision, and service that are not only universal but also have distinctiveness rooted in faith and spirituality.